PENGARUH LITERASI KEUANGAN DAN LITERASI DIGITAL TERHADAP KESADARAN PENIPUAN INVESTASI PADA MAHASISWA - Lestari, Sri Kusuma; Hindrayani, Aniek; Sangka, Khresna Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.04.TAHUN.2025, 2025)
Having the knowledge, the understanding, and the ability to manage finances independently is an ability that every individual must master. One of these abilities is through investing. In Indonesia, the number of investors has increased since 2019 whereas in February 2023 the number of investors has reached 10.6 million investors. This increase in the number of investors is followed by many cases of investment scams, one of which is the many victims of binary option platform scams and trading bot scams. This scam does not only occur in the general public, but can also happen to students from universities. The many victims of scams can be caused by a lack of financial literacy and digital literacy in the community which is a problem because many are interested in becoming investors but do not have enough knowledge and understanding, thus increasing the possibility of investment scams. This study aims to determine the effect of financial literacy and digital literacy partially on the awareness of investment scams in students in Solo Raya. Data collection in this study used the Guttman scale and the Likert scale which were converted to dummy variables and analysed using binary logistics. The results of this study found that financial literacy and digital literacy partially have a positive and significant effect on investment scams awareness amongst college students studying in Solo Raya